Combination Therapy with Continuous Three-in-One Femoral Nerve Block and Periarticular Multimodal Drug Infiltration after Total Hip Arthroplasty - Tomonori Tetsunaga; Tomoko Tetsunaga; Kazuo Fujiwara; Hirosuke Endo; Toshifumi Ozaki (Pain Research and Management)
Background. Various postoperative pain relief modalities, including continuous femoral nerve block (CFNB), local infiltration analgesia (LIA), and combination therapy, have been reported for total knee arthroplasty. However, no studies have compared CFNB with LIA for total hip arthroplasty (THA). The aim of this study was to compare the efficacy of CFNB versus LIA after THA. Methods. We retrospectively reviewed the postoperative outcomes of 93 THA patients (20 men, 73 women; mean age 69.2 years). Patients were divided into three groups according to postoperative analgesic technique: CFNB, LIA, or combined CFNB+LIA. We measured the following postoperative outcome parameters: visual analog scale (VAS) for pain at rest, supplemental analgesia, side effects, mobilization, length of hospital stay, and Harris Hip Score (HHS). Results. The CFNB+LIA group had significantly lower VAS pain scores than the CFNB and LIA groups on postoperative day 1. There were no significant differences among the three groups in use of supplemental analgesia, side effects, mobilization, length of hospital stay, or HHS at 3 months after THA. Conclusions. Although there were no clinically significant differences in outcomes among the three groups, combination therapy with CFNB and LIA provided better pain relief after THA than CFNB or LIA alone, with few side effects.